Hydrogen Peroxide Signaling in Plant Development and Abiotic Responses: Crosstalk with Nitric Oxide and Calcium - Niu, Lijuan; Liao, Weibiao (Frontiers in Plant Science, 2016)
Hydrogen peroxide (H2O2), as a reactive oxygen species, is widely generated in many biological systems. It has been considered as an important signaling molecule that mediates various physiological and biochemical processes in plants. Normal metabolism in plant cells results in H2O2 generation, from a variety of sources. Also, it is now clear that nitric oxide (NO) and calcium (Ca2+) function as signaling molecules in plants. Both H2O2 and NO are involved in plant development and abiotic responses. A wide range of evidences suggest that NO could be generated under similar stress conditions and with similar kinetics as H2O2. The interplay between H2O2 and NO has important functional implications to modulate transduction processes in plants. Moreover, close interaction also exists between H2O2 and Ca2+ in response to development and abiotic stresses in plants. Cellular responses to H2O2 and Ca2+ signaling systems are complex. There is quite a bit of interaction between H2O2 and Ca2+ signaling in responses to several stimuli. This review aims to introduce these evidences in our understanding of the crosstalk among H2O2, NO, and Ca2+ signaling which regulates plant growth and development, and other cellular and physiological responses to abiotic stresses.